2018
DOI: 10.1177/1534735418790382
|View full text |Cite
|
Sign up to set email alerts
|

Modified Citrus Pectin as a Potential Sensitizer for Radiotherapy in Prostate Cancer

Abstract: Background: Radiotherapy is one of the primary therapies for localized prostatic carcinoma. Therefore, there is an emerging need to sensitize prostatic cancer cells to chemotherapy/radiotherapy. Modified citrus pectin (MCP) is an effective inhibitor of galectin-3 (Gal-3), which is correlated with tumor progression, proliferation, angiogenesis, and apoptosis. Purpose: This study was directed to evaluate the efficacy of combining ionizing radiation (IR) with MCP on PCa cells. Study Design: Effects of treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…The released Galectin-3 can bind to components of extracellular matrix and its membrane counterparts of other cells, which have in a wide range of biological events including cellular homeostasis, immune function, angiogenesis, tumor invasion and metastasis 25 . Galectin-3 has been reported as a diagnostic or prognostic marker linked to metastasis in many types of cancer such as thyroid 26,27 , breast cancer 28 , melanoma 29 , lung cancer 30 , sarcoma 31 , gastric cancer 32 , prostate cancer 33 and oral tongue cancer 34 . Here, we showed that Galectin-3 was greatly expressed in highly metastatic NPC cells compared to lowly metastatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…The released Galectin-3 can bind to components of extracellular matrix and its membrane counterparts of other cells, which have in a wide range of biological events including cellular homeostasis, immune function, angiogenesis, tumor invasion and metastasis 25 . Galectin-3 has been reported as a diagnostic or prognostic marker linked to metastasis in many types of cancer such as thyroid 26,27 , breast cancer 28 , melanoma 29 , lung cancer 30 , sarcoma 31 , gastric cancer 32 , prostate cancer 33 and oral tongue cancer 34 . Here, we showed that Galectin-3 was greatly expressed in highly metastatic NPC cells compared to lowly metastatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with other reports, the authors also showed that GCS-100, an antagonist of Gal-3, induced cancer cell death [ 190 , 191 , 192 ], boosted tumor-infiltrating T lymphocyte secretion of IFN-gamma [ 143 ], and increased prostate cancer sensitivity to cisplatin [ 193 ]. Similarly, an effect was observed in response to modified citrus pectin (MCP) on cancer [ 67 , 95 , 194 , 195 ]; however, MCP can also be used for other Gal-related disease treatments, such as decreasing Gal-3 levels in type 2 diabetes [ 196 ], decreasing doxorubicin-induced cardiovascular diseases [ 197 ], ameliorating cardiac dysfunction [ 198 ], and improving ischemic heart failure [ 199 ]. In addition, the calixarene derivative compound “OTX-008” was designed as a Gal-1 inhibitor [ 200 ].…”
Section: Available Inhibitors For Targeting Galectinsmentioning
confidence: 99%
“…Moreover, MCP reduced prostate cancer cell viability and synergistically enhanced cell sensitivity to ionizing radiation [10]. Inhibition with the MCP of extracellular Gal-3 decreased colon cancer cell migration [9].…”
Section: Cancermentioning
confidence: 99%